2023
DOI: 10.1111/bdi.13321
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma and cognitive functioning in mood disorders: A systematic review

Abstract: Background Cognitive impairment is a core feature of mood disorders and has been identified as an important treatment target. A better understanding of the factors contributing to cognitive impairment in mood disorders would be beneficial in developing interventions to address cognitive impairment. One key factor is childhood trauma. The aim of this review was to systematically synthesise and review research examining associations between reported childhood trauma and cognitive functioning in mood disorders. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Furthermore, CT was found not only to affect the SC of schizophrenia patients but also to contribute to the cognitive impairment of bipolar disorder patients, specifically in working memory and executive function ( 60 ). A comprehensive review of 1,723 mood disorders and 797 healthy controls also confirmed that CT has a certain impact on the cognitive and executive functions of mood disorders ( 61 ).…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, CT was found not only to affect the SC of schizophrenia patients but also to contribute to the cognitive impairment of bipolar disorder patients, specifically in working memory and executive function ( 60 ). A comprehensive review of 1,723 mood disorders and 797 healthy controls also confirmed that CT has a certain impact on the cognitive and executive functions of mood disorders ( 61 ).…”
Section: Discussionmentioning
confidence: 86%
“…The association between borderline personality disorder and major depression disorder was partially explained by shared pathological personality traits, which may be underpinned by disturbances of cognitive control [ 32 ]. Cognitive dysfunction is associated with childhood trauma in mood disorders [ 50 ]. Childhood trauma can induce alterations in the hypothalamic-pituitary-adrenal axis, neurotransmission, endogenous opioid systems, and neural plasticity, which increase an individual’s susceptibility to developing borderline personality disorder [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence supports that childhood maltreatment increases the risk of mood disorders substantially. 8,9 In addition, childhood maltreatment is associated with an earlier age at onset of mood disorder, a more severe illness course, impaired social functioning 10 including cognitive difficulties, 11 more perceived stress, lower quality of life, 12 sexual health problems, 13,14 and physical diseases. 15,16 The landmark study by Caspi et al 17,18 showed that the impact of severe life events seems mediated through genetic variation, variations that contributed to an increased vulnerability in maltreated children.…”
Section: Introductionmentioning
confidence: 99%